THE RELATIONSHIP BETWEEN PARENTING STYLE AND CHILDREN LEARNING DISCIPLINE - Nurhadi Nurhadi (AL-ISHLAH: Jurnal Pendidikan, 2020)
The purpose of this study is to determine parenting as applied by parents in Kelurahan Rawang Empat and to what extent parents' understanding of the relationship between parenting and children's learning discipline, as well as the causes of parenting. This research uses descriptive method with correlational research analysis techniques. Based on the analysis conducted showed that in the Rawang Empat sub-district Bandar Petalangan sub-district Pelalawan District parenting patterns in primary school children with an average value of 27.43 included in the category of "good enough" which is in the interval 25-28. While the level of discipline of elementary school children with an average value of 23.13 is included in the category of "sufficient discipline" that is at intervals of 21-23. By using product moment correlation analysis the results of hypothesis analysis show that the value of rxy = 0.953 is in a positive direction. The relationship between parenting style and the level of discipline of learning of elementary school children is included in the category of "very strong" at intervals of 0.80-1,000. The research data also showed that tcount = 14.416, while ttable at a significance level of 5% = 0.433 and ttable at a significance level of 1% = 0.549. It can be seen that tcount is greater than ttable. Thus it can be concluded that there is a significant relationship between parenting and the level of discipline of elementary school children in Rawang Empat Village, Bandar Petalangan District, Pelalawan Regency.